Perancangan Sistem Informasi Geografis (Sig) Pemetaan Destinasi Wisata Menggunakan Metode Agile Pada Kecamatan Sadananya Berbasis Web Dengan Metode Agile - Afriyandi, Rizal; Mulyana, Dadan; Dwicahya Supriatman, Rian (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2025)
The goal of this study was to achieve the results of a web-based geographical information system on tourist destinations mapping in Sadananya subdistrict. The information about tourist places based on the data from the manager of Sadananya sub-district. This geographical information system mapping tourist destinations is aimed at facilitating tourists access information about tourist spots in Sadananya subdistrict, and therefore it is hoped that it can raise touristic potentials within this area. The process of building a web-based Geographical Information System (GIS) used the Agile method with two stages in it, namely Requirements and Design. In using Agile Method, flexibility in system development enables adaptations to users’ and environmental changes. System test results indicated that the SIG developed can provide accurate and relevant information about tourism in Sadananya subdistrict municipalities. Through this digital map, places of interest will be easy for users to find and they can also get the best navigations going to these places.